The Party mobilization military reservists of communists in the Khanty-Mansiysk National District on 1941–1942 of the Great Patriotic War - E. V. Leshukova (Омский научный вестник: Серия "Общество. История. Современность")
The article based on the materials of the State Archive of the Socio-Political History of the Tyumen region examines one of the little-studied aspects of mobilization measures carried out at the initial stage of the Great Patriotic War on the territory of the Khanty-Mansiysk National District, which until August 1944 was part of the Omsk and then the Tyumen regions. Based on a selective analysis of the numerical, age, professional composition, seniority of the leadership of communists and Komsomol members, called up by the district and district military registration and enlistment offices in the ranks of the Red Army from June 1941 to July 1942, the conclusion is made about the nature of the mobilization practice of the party and economic elite, culture and education workers Ugra and the ambiguity of the influence of mobilization along the party line on the life of the district in the war and post-war times.